\(Dy^3+-Doped\) Glass-Ceramic Fibers: A Promising Gain Fiber towards Tunable Yellow Laser - Qianyi Chen; Minbo Wu; Puxian Xiong; Yajing Zhao; Shuhang Tian; Yao Xiao; Yongsheng Sun; Dongdan Chen; Shanhui Xu; Zhongmin Yang (Current Innovations in Chemical and Materials Sciences Vol. 1, 2023)
Yellow lasers are of great interest in biology, medicine and display technology. However, nonlinear emission of near-infrared lasers at yellow still presents particularly complex optical alignment to date and the direct access of yellow laser is eagerly damanded. Here, to the best of our knowledge, we demonstrate the fabrication of a NaLa(WO4)2: Dy3+ glass-ceramic fiber (GCF) for the first time. More importantly, the emission band of the GCF, which is around 575 nm, has a wide full-width half maximum (FWHM) of 18 22 nm, which is remarkably larger than that of the Dy3+-doped YAG crystal (<7 nm). The precursor fiber (PF) was drawn using the molten core drawing (MCD) method. In particular, benefiting from the in situ nanocrystals fabricated in the amorphous fiber core after thermal treatment, the resultant glass-ceramic fiber exhibits a five-times enhancement of luminescence intensity around 575 nm, compared with the precursor fiber, while retaining its broadband emission. Overall, this work is anticipated to offer a high potential GCF with prominent bandwidth for the direct access of a tunable yellow laser.